Women's Experiences of Managing Work and End-of-Life Care: Challenges, Rewards and Recommendations for Vocational Psychologists. (February 2021) - O'Brien, Karen M.; Yang, NaYeon; Jankauskaite, Greta
End-of-life care is a form of unpaid care work that is primarily the responsibility of women and can affect their career development, employment, finances, and vocational success. This paper provides a review of the literature on the career and economic effects of providing unpaid end-of-life care for women caregivers. Illustrative reflections from women caregivers highlight challenging and positive aspects of providing end-of-life care. Challenges identified by the women caregivers included managing conflicting demands among work, home and caregiving as well as experiencing emotional strain, financial burden and economic instability. In addition, work schedules had to be altered and career trajectories were interrupted. Interestingly, caregivers reported receiving support from their employers and co-workers and few work-related benefits were used. Despite the many challenges in managing work and end-of-life care, many participants felt positively about their ability to provide a caring environment for a loved one at the time of their death. Recommendations for individual, familial, workplace, and societal changes related to unpaid end-of-life care will be provided.